Prospects for the use of Bacillus anthracis toxin in cancer therapy - A. P. Rodionov; S. V. Ivanova; E. A. Artemeva; L. A. Melnikova (Ветеринария сегодня)
Cancer is one of the major causes of death in pet animals and humans worldwide. The contraindications and side effects associated with conventional cancer therapies heighten the importance of research aimed at finding new ways to combat cancer. One of the promising methods for the treatment of oncological diseases is the use of components of bacterial toxins, in particular the toxins of Bacillus anthracis, the causative agent of anthrax. Lethal factor is the main virulence factor of the anthrax pathogen, which is a zinc-dependent metalloprotease, the substrate for which is intracellular MAPK signaling pathways widely present in cancer cells. This review focuses on discussing the experience of foreign researchers in the application of Bacillus anthracis lethal factor in cancer therapy. The paper presents data from the studies that characterize the structure and functions of the lethal factor, reflect the results of its application on cancer cells both as a part of anthrax toxin and as a separate unit, reveal its therapeutic potential. The analysis of literature demonstrated good prospects for the potential use of the lethal factor to combat such types of cancer as liver, lung, colon, breast, pancreatic, ovarian, prostate, stomach and nervous system cancers. However, despite the impressive results, further in-depth research is needed in this area concerning selection of optimum doses of the lethal factor, determination of sensitivity of different types of cancer to it, investigation of its effects on other body tissues and interaction with the immune system during therapy.